Slow Down, Redesign, and Accelerate: Adaptations and Resilience on Business Sales Transformation amid COVID-19 crisis - Candello, Heloisa; Ferreira, Juliana Jansen; Vasconcelos, Marisa Affonso; Santana, Vagner Figueredo de; Paula, Rogério de; Pinhanez, Claudio (2020)
ABSTRACT The coronavirus pandemic forced all the world to find new ways to 'get the work done.' Social isolation in particular shifts the work to primarily remote, which compelled us to reassess a particular set of work practices that were before inherently personal and hightouch in nature. Business-to-Business (B2B) sales practices have been already under digital transformation in the light of technology advances (e.g., advances in Social-Computing, Artificial Intelligence, and Blockchain technology), prior to COVID-19. In the new reality, plans had to be reviewed and strategy recreated while business kept going. In this position paper, we start a discuss on the impacts of the COVID-19 on B2B sales work practices and existing supporting technologies. We present a set of research questions to guide the investigation of B2B work practices in a post-COVID-19 world, considering the lessons learned during the crisis and how they impacted B2B digital transformation plans. ABOUT THE AUTHOR/S Heloisa Candello IBM Research heloisacandello@br.ibm.com https://scholar.google.com.br/citations?user=8B5GrTYAAAAJ&hl=en Juliana Jansen Ferreira IBM Research jjansen@br.ibm.com https://scholar.google.com/citations?user=oJgnxQ4AAAAJ&hl=en Marisa Affonso Vasconcelos IBM Research marisaav@br.ibm.com Vagner Figueredo de Santana IBM Research vagsant@br.ibm.com https://scholar.google.com.br/citations?user=f0QLYG8AAAAJ&hl=en Rogério de Paula IBM Research ropaula@br.ibm.com https://scholar.google.com.br/citations?user=Sqgh138AAAAJ&hl=en Marisa Affonso Vasconcelos IBM Research marisaav@br.ibm.com Claudio Pinhanez IBM Research csantosp@br.ibm.com https://scholar.google.com.br/citations?user=YPq3ax4AAAAJ&hl=en New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).